Students’ perspectives on the 4/3/2 technique and self-assessment to improve English speaking fluency - Jardel Coutinho dos Santos; María Rossana Ramírez-Avila (Universitas Syiah Kuala, 2023)
Understanding students’ perspectives and differentiating classroom practices based on student needs are considered effective educators’ primary purposes in improving the foreign language learning process. How teachers conduct and teach their classes significantly affects how students cope with their learning. For this reason, this phenomenological study aimed to identify the perspectives among 12 Ecuadorian ninth graders on the 4/3/2 technique and self-assessment used to improve their English-speaking fluency during a five-week class. The data were collected through interviews and visual narratives and analyzed using grounded theory. The results of the study show that the 4/3/2 technique presented three categories (I learned because I repeated; I increased my speaking speed and decreased word repetitions; I got nervous when I had to speak faster). Self-assessment presented two categories (I learned from my mistakes; We were aware of our progress, which motivated us). Thus, this study has shown the importance of identifying students’ perspectives on the two learning strategies used in class. By doing this, teachers can select the appropriate technique for that specific learning context based on the students’ perceptions and foreign language theories. Further research is still necessary for the Ecuadorian context to explore how students’ perspective on the teachers’ learning methodologies affect them, especially their emotions.